Community Resilience and Suicide Prevention: A Review of Policy-Aligned Intervention Strategies - Lestari, Putri Ayu; Fitriyah, Aidatul (Sinergi International Journal of Psychology, 2025)
Community-based suicide prevention programs are gaining recognition for their holistic, participatory, and context-sensitive approaches to reducing suicide rates. This narrative review aims to synthesize recent empirical findings on the effectiveness of such interventions, especially in integrating local engagement, educational and religious institutions, sociocultural strategies, and comparative international practices. Utilizing a structured literature search across Scopus, PubMed, and Google Scholar, relevant peer-reviewed articles were selected and analyzed thematically. The results demonstrate that community-driven programs effectively reduce suicide risks by enhancing early detection, emotional support, and crisis response capacities. Engagement of schools and religious leaders fosters mental health literacy, while cultural adaptation improves acceptance and inclusivity. International comparisons reveal that while developed countries benefit from advanced infrastructure and formal systems, developing nations often succeed through community innovation and resilience. Nevertheless, systemic challenges—such as policy gaps, mental health service disparities, and social stigma—persist across contexts. These findings reaffirm the need for a multisectoral, collaborative framework that integrates policy support, community empowerment, and sustainable funding. Strategic use of digital tools and long-term program evaluation is essential. This review contributes to the growing body of knowledge advocating for community-centric, culturally responsive, and structurally supported suicide prevention models.